Hot, flat, and crowded : why we need a green revolution, and how it can renew America - Friedman, Thomas L. (New York : Farrar, Straus and Giroux, 2008)
Examines America's loss of focus and national purpose since 9/11, and the global environmental crisis, and shows how the solutions to these two problems are linked.
pt. 1. Where we are -- 1. Where birds don't fly -- 2. Today's date : 1 E.C.E. Today's weather : hot, flat, and crowded -- pt. 2. How we got here -- 3. Our carbon copies (or, Too many Americans) -- 4. Fill 'er up with dictators -- 5. Global weirding -- 6. The age of Noah -- 7. Energy poverty -- 8. Green is the new red, white, and blue -- pt. 3. How we move forward -- 9. 205 easy ways to save the Earth -- 10. The energy Internet : when IT meets ET -- 11. The Stone Age didn't end because we ran out of stones -- 12. If it isn't boring, it isn't green -- 13. A million Noahs, a million arks -- 14. Outgreening al-Qaeda (or, Buy one, get four free) -- pt. 4. China -- 15. Can Red China become Green China? -- pt. 5. America -- 16. China for a day (but not for two) -- ch. 17. A Democratic China, or a banana republic? -- Acknowledgments -- Index.
Includes index.
Keywords: Green movement -- United States; Green technology -- United States; Climatic changes; Power resources -- Environmental aspects; Environmental policy -- United States; Energy policy -- United States; United States -- Environmental conditions; United States -- Social conditions -- 1980-2020.; Energy policy -- United States; Climate -- Government policy -- United States; Energy resources -- United States; Renewable energy resources -- United States; Environmental policy -- United States